Gallium 68 PSMA-11 PET/MR imaging in patients with intermediate- or high-risk prostate cancer - Park, Sonya Youngju; Giesel, Frederik L. (Radiology, 2018)
PurposeTo report the results of dual-time-point gallium 68 (68Ga) prostate-specific membrane antigen (PSMA)-11 positron emission tomography (PET)/magnetic resonance (MR) imaging prior to prostatectomy in patients with intermediate- or high-risk cancer.Materials and MethodsThirty-three men who underwent conventional imaging as clinically indicated and who were scheduled for radical prostatectomy with pelvic lymph node dissection were recruited for this study. A mean dose of 4.1 mCi ± 0.7(151.7 MBq ± 25.9) of 68Ga-PSMA-11 was administered. Whole-body images were acquired starting 41-61 minutes after injection by using a GE SIGNA PET/MR imaging unit, followed by an additional pelvic PET/MR imaging acquisition at 87-125 minutes after injection. PET/MR imaging findings were compared with findings at multiparametric MR imaging (including diffusion-weighted imaging, T2-weighted imaging, and dynamic contrast material-enhanced imaging) and were correlated with results of final whole-mount pathologic examination and pelvic nodal dissection to yield sensitivity and specificity. Dual-time-point metabolic parameters (eg, maximum standardized uptake value [SUVmax]) were compared by using a paired t test and were correlated with clinical and histopathologic variables including prostate-specific antigen level, Gleason score, and tumor volume.ResultsProstate cancer was seen at 68Ga-PSMA-11 PET in all 33 patients, whereas multiparametric MR imaging depicted Prostate Imaging Reporting and Data System (PI-RADS) 4 or 5 lesions in 26 patients and PI-RADS 3 lesions in four patients. Focal uptake was seen in the pelvic lymph nodes in five patients. Pathologic examination confirmed prostate cancer in all patients, as well as nodal metastasis in three. All patients with normal pelvic nodes in PET/MR imaging had no metastases at pathologic examination. The accumulation of 68Ga-PSMA-11 increased at later acquisition times, with higher mean SUVmax (15.3 vs 12.3, P < .001). One additional prostate cancer was identified only at delayed imaging.ConclusionThis study found that 68Ga-PSMA-11 PET can be used to identify prostate cancer, while MR imaging provides detailed anatomic guidance. Hence, 68Ga-PSMA-11 PET/MR imaging provides valuable diagnostic information and may inform the need for and extent of pelvic node dissection.© RSNA, 2018Online supplemental material is available for this article.
Gesehen am 21.02.2020